Faith and reason: their roles in religious and secular life - Crosby, Donald A. (State Univ. of New York Press, 2011)
Initial sketch of a concept of faith -- Facets of faith -- Faith and knowledge -- Faith and scientific knowledge -- Faith and morality -- Secular forms of faith -- Crises of faith -- My personal journey of faith